Epistemology of practice in the field of education: challenges, possibilities and perspectives - Bonatto Rufino, Luiz Gustavo; Neto, Samuel de Souza [UNESP] (Univ Brasilia, 2022)
This study aimed to analyze some of the potentialities, limitations, challenges and perspectives related to the concept of epistemology of practice in the educational field. We sought, through a theoretical essay, to substantiate the understanding of practice in the social sciences in general and the representations linked to the concept of epistemology of practice, traversing part of its origins, criticisms and current perspectives. It is concluded that it is necessary to encourage the development of research on the concept of epistemology of practice, whose analytical paradigm has potential to contribute to the development of pedagogical practice and the production of knowledge in the educational field.
Keywords: Epistemology; Practice; Professionalization; Teaching; Epistemology of Practice